1983
DOI: 10.1007/bf01543175
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of cell cycle-dependent gamma ray-sensitive Chinese hamster ovary cell

Abstract: A technique for the isolation of gamma ray-sensitive Chinese hamster ovary (CHO) cell mutants is described, which uses nylon cloth replica plating and photography with dark-field illumination to directly monitor colonies for growth after gamma irradiation. Two gamma ray-sensitive mutants were isolated using this method. One of these cells (XR-1) had a two-slope survival curve: an initial steep slope and then a flattening of the curve at about 10% survival. Subsequently, it was found that this cell is sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
51
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(56 citation statements)
references
References 25 publications
5
51
0
Order By: Relevance
“…This correlation of drug sensitivity under hypoxia with the rate of drug metabolism did not hold for the two CHO mutants, XR-1 and V-3, which are sensitive to ionising radiation due to a deficiency in DNA double strand break rejoining (Stamato et al, 1983;Whitmore et al, 1989). Complementation studies showed that both these cell lines represent separate DNA repair deficient mutants.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This correlation of drug sensitivity under hypoxia with the rate of drug metabolism did not hold for the two CHO mutants, XR-1 and V-3, which are sensitive to ionising radiation due to a deficiency in DNA double strand break rejoining (Stamato et al, 1983;Whitmore et al, 1989). Complementation studies showed that both these cell lines represent separate DNA repair deficient mutants.…”
Section: Discussionmentioning
confidence: 94%
“…CHO V-3 cells (Whitmore et al, 1989) were obtained courtesy of G.F. Whitmore, U. of Toronto. XR-1, a cell cycle specific gammaray sensitive CHO cell mutant (Stamato et al, 1983) (Figure 7b). The cell lines SCCVII and AT5BI displaying the highest sensitivity to SR 4233 under hypoxia also metabolised the drug to the greatest extent.…”
mentioning
confidence: 99%
“…An XRCC3 gene knockout in the human colon cancer cell line HCT116 has been reported recently, and the XRCC3-deficient cells showed ϳ2-fold excess sensitivity to MMC (58 (59,60) that is associated primarily with the late S/G 2 phase (49). By contrast, the NHEJ-defective Chinese hamster ovary mutants for XRCC4, Ku86, and DNA-PKcs (the XR-1, xrs5/6, and V3 cell lines, respectively) are highly sensitive to IR in G 1 and early S phases compared with the wild type but are more IR-resistant in late S/G 2 (61)(62)(63)(64). A similar pattern was reported for murine pre-B cells carrying the scid mutation (65).…”
Section: Rad51c Dynamically Influences the Protein Levels Of Other Rad51mentioning
confidence: 99%
“…CHOK1 (a glycine auxotroph of CHO cells), 4364A (a proline and glycine auxotroph of CHOK1 [17]), xrs 5 (18) and XR-1 (7,9,34,35) (hamster DNA double-strand break repair-deficient mutant cell lines), and A x W-1 (a hybrid of XR-1 and a wild-type human line [8]) were obtained from A. J. Giaccia (Stanford University) and were cultured in RPMI 1640 medium. V-G8 and V-E5 (hamster ataxia telangiectasia-like mutants), the wild-type parental line V79 (39), and V79B and XR-V9B (40) were maintained in Ham's F-10 medium.…”
mentioning
confidence: 99%
“…It is the parental line from which XR-1 was originally derived by mutagenesis (35). Recombination in 4364A was 0.3% for signal joint formation, as determined with substrate pJH200.…”
mentioning
confidence: 99%